Effects of water stress on the accumulation of soluble carbohydrates and growth patterns of corn - Rossiello, Roberto O.P.; Fernandes, Manlio S.; Flores, João P.O. (Pesquisa Agropecuaria Brasileira, 2014)
The effects of progressive soil dessiccation on the relative water content (RWC), leaf area, relative growth rate (RGR), net assimilation rate (NAR) and levels of soluble carbohydrates in corn (Zea mays L.) were studied under greenhouse conditions. Progressive soil dessiccation reduced dry matter accumulation and NAR. Soluble carbohydrate levels increased sharply with a 7% RWC decrease. There was a negative relationship between soluble carbohydrates and RGR. The total dry matter accumulation of plants under stress did not change significantly during the period (five days) because the reduction in dry matter of the tops was compensated by an increase in dry matter of the roots. As there was a fall in NAR, it appears that a translocation to the roots of soluble carbohydrates previously accumulated in the tops occurred, which was responsible for the increase in dry matter of the roots. It was stressed the need for a better understanding of the relationships between carbohydrates accumulation, translocation and respiratory ratios under conditions of water stress.